Analysis of The Difference of Abnormal Return And Trading Volume Activity on The Announcement of The Merger - Muhammad Kurnia Rahman Abadi; Marrotul - Fahrie (LPPM STIE PERTIBA Pangkalpinang, 2021)
Abstract This research is based on the announcement of the merger of Bank Syariah Indonesia, where the event is considered to have information content that is able to influence the decisions of investors in the capital market. The purpose of this study was to determine the difference of market reaction on the announcement of the merger of Bank Syariah Indonesia in companies listed in the Jakarta Islamic Index 70. The method used in this research is quantitative research with an event study approach, and dat analyzed uses a Wilcoxon Sign Rank Test. The results of these tests indicate that there is no difference in abnormal returns and there are differences in trading volume activity during the observation period before and after the merger. Keywords: Abnormal Return, Trading Volume Activity, Merger Announcement.